Developing successful trust-based international exchange relationships - Katsikeas, Constantine S; Skarmeas, Dionysis; Bello, Daniel C (Journal of International Business Studies, 2009)
Trust is a central construct in relationship marketing. Yet the literature provides mixed empirical evidence on the trust–performance linkage. Also, there is limited research on how to build trusting international buyer–seller relations. We develop a comprehensive model integrating performance-enhancing mechanisms and antecedent processes of trust in import–export relationships. Our survey results from importers trading with overseas manufacturers suggest that existing levels of trust have a positive effect on relationship performance outcomes achieved 1 year later. Importantly, trust takes on greater importance in enhancing performance under conditions of high interdependence, whereas in circumstances of low interdependence trust has no discernible effect. The findings also indicate that interfirm psychic distance, internal uncertainty, and exporter transaction-specific assets and opportunism are related to importer trust. Implications for academics and practitioners are addressed.